SPECIFICITY OF TEACHING ACTIVITY AS A FACTOR OF PSYCHOSOMATIC RISK - Galina Timoshenko; Elena Leonenko; Elena Pakhtusova (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the possibility of providing specific social factors that shape the specificity of psychosomatic professional risks. The authors identify a vertical position of man in his social interaction as a factor to form psychosomatic risks which are specific to teaching activity. For each specific vertical position of man authors describe the specific mechanisms of formation of various psychosomatic risks, based on the contents of the main experiences peculiar to this position. The content of such main experiences in related to the author s concept of main emotions.